AUTO-COMBUSTION SYNTHESIS OF Al-DOPED ZnO NANOPARTICLES: STRUCTURAL AND ENERGY BAND GAP ENHANCEMENT - Suan, M.S.M.; Yusof, I.M.; Nurdin, I. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Auto-combustion reaction has been developed as a new route in synthesizing ZnO and Al-doped ZnO nanoparticles with improved structural, and optical properties. In this work, the effects of Al doping concentrations and different calcination temperatures were investigated. The Zn(NO3)2 aqueous solution was mixed with Al(NO3)3, citric acid, and ammonia aqueous solutions to obtain a series of mixtures with varied Al molarity concentration, x from 0 to 0.5. The highly exothermic single-step auto-combustion reaction at around 230 °C has transformed the mixture into fine black ashes which yielded white powder during calcinated at various calcination temperature, Tcal for 1 h in a normal furnace atmosphere. The XRD results revealed that the transformation of amorphous ZnO ashes into highly crystalline ZnO with a hexagonal structure was completed at Tcal ≥ 700 °C where the c lattice constant in the samples was increased by the increases of Al doping concentration. The SEM images of the Zn1-xAlxO samples calcined at Tcal = 700 °C showed a dense and highly packed of ZnO nanoparticles due to the increased of Al diffusion in ZnO and higher grain growth rate of ZnO. The energy band gap obtained from UV-vis results was significantly improved in Zn1-xAlxO samples calcined at Tcal = 700 °C attributed to the well-controlled of Al doping concentration in effectively adjusting the electronic properties of the ZnO nanoparticles.